An Industrial systems design analysis on Liberty Marble and Granite, Inc. - Balaguer, Aimee O.; Flores, Ma. Criselda M.; Gonzales, Cheryl Victoria G.; Javier, Nidalin C. (Diliman, Quezon City College of Engineering, 2005)
The focus of the project study was the application of a total systems approach to evaluate the key strategies used by Liberty Marble & Granite Inc. (LMGI). LMGI is engaged in the design, estimation, and installation of stone products. In order to effectively evaluate the company's current operations, the goals of the company, in terms of its mission and vision as well as its systems and procedures, were documented by conducting site interviews. Afterwards, the company's performance and current position in its industry were assessed by means of environmental scanning, industry analysis and competitor analysis. Various tools such as SWOT Analysis, Seven S Model and Porter's Five Forces were used. Gap Analysis and Prioritization Matrices were presented to illustrate the strategic needs of the company that needed to be addressed, in order to attain its desired goals. The results of the various tools, together with the results of the Gap and Prioritization Matrices, were integrated. Two general strategies were identified, specifically the following: the employment of Low Cost Strategy, and the strengthening of its position in the retail market through Liberty Stile (a sister company involved in retail ceramic tiles) by using a Market Penetration Strategy. These proposed strategies were then translated to operational procedures that could be applied by the company. To address the first proposed strategy, a marketing plan for Liberty Stile was prepared to improve the level of business. To effectively employ the Low Cost Strategy, the group formulated several operational recommendations, namely: procedures and guidelines for supplier accreditation, installation operations, and quality checking at the source. Implementation guidelines, Gantt Chart, proposed forms, and an initial supplier database were provided by the group as part of the project outputs to facilitate LMGI's execution of the recommendations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Liberty Marble & Granite Inc. (LMGI); Stone industry and trade; System design